Queen of dreams - Divakaruni, Chitra Banerjee 1956- (London Abacus, 2005)
The award-winning author of MISTRESS OF SPICES and SISTER OF MY HEART returns with a luminous novel in her signature style - a tale of family, love and identity and the mystical story of a woman caught between two worlds.
This paperback edition published in December 2005.
First published in Great Britain in 2005 by Abacus.
First published in the United States of America in 2004 by Doubleday.
UCWS-3058g donated by Dr. Thelma B. Kintanar - July 2017
Keywords: East Indian American women -- Fiction; Mothers and daughters -- Fiction; Divorced mothers -- Fiction; Dreams -- Fiction; California -- Fiction; India -- Fiction; Psychological fiction; Domestic fiction